Pemanfaatan Game Edukasi Wordwall Sebagai Evaluasi Pembelajaran Bahasa Arab Secara Daring di MA NURUL ISLAM Sekarbela - Izmiatun Azizah; Suparmanto; Hilal Kurnia; Ahmad Muzandi; Rizwanul Abror (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2026)
Low engagement in Arabic leangue evaluations at MA Nurul Islam Sekarbela was the main reason for conducting this Classroom Action Research (CAR). Conventional evaluation methods that rely solely on individual worksheets tend to be rigid and the may cause students to lose interest. To address this issue, the study aimed to explain how the Wordwall educatonal game functions as an interactive assessment tool to enhance students' motivation. The research subjects consisted of 10th-grade students at MA Nurul Islam Sekarbela. Data were collected through observation, learning motivation questionnaires, and automated test result from the Wordwall platform. This study was conducted in two face-to-face cycles, during which the evaluation process utilized the students’ personal devices. Cycle I applied the Anagram template combined with the leaderboard feature. The results showed a significant in crease in students’ learning motivation at each stage. In the initial or pre-cycle phase, the percentage of students’ learning motivation was 20%. After the implementation of cycle I, the percentage increased to 50%. The highest results was observed in Cycle II, Where students’ learning motivation rose to 80% and achieved the research success indicatoes. Thus, the implementation of the Wordwall educational game, supported by digital media, proved effective in enhancing students’ learning motivation in Arabic language assessment.